Exploring Brand Experience Dimensions for Cities and InvestigatingTheir Effects on Loyalty to a City - (:unkn) unknown (My University, 2014)
0

The competitive environment in terms of tourists and investment attraction requires the strategic management of cities. The marketing literature in this topic relates to different dimensions, most importantly, the image, identity, and branding of a city, satisfaction, and the degree of loyalty that the city inspires. This study, as the major contribution to literature, aims to introduce a new competitive tool, 'brand experience' dimension to the city marketing literature based on Schmitt's (1999) and Brakus et al.'s (2009) experience dimensions, and to reveal its use in measuring loyalty to a city. For this purpose, two consecutive studies have been conducted. The first study aims to explore the dimensions of brand experience in cities, and the second investigates the effects of these dimensions on "loyalty to a city". The findings of the study reveal that city experiences consist of five dimensions: Social Activities & Leisure Time Experience, Affective Experience, and Taste Experiences, Disturbing Sensory Experience and Nature-Related Experience. Three of these dimensions (Affective experience, taste experience (food identified with city), nature-related experience) are found to positively affect loyalty to a city
Keywords: Tarih